Positive electrode material, method for preparing the same, and electrochemical device
Patent Information
- Application Number
- CN202611328571.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0002]尖晶石锰酸锂(LiMn2O4)资源丰富、成本低廉、安全性好且工作电压高,在锂离子电池正极材料领域一直备受关注,但其循环寿命和高温稳定性较差的问题始终制约着大规模商业化应用
1、基体为镁掺杂的尖晶石锰酸锂,其中Mg2+替代部分Mn3+并占据八面体位点,尖晶石骨架的稳定性得到增强,充放电过程中因Mn3+浓度变化所引发的结构畸变得到了抑制,Mn溶出的速率有所降低,基体的结构可逆性和循环稳定性由此得到改善。
Smart Images

Figure CN123017943A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of new energy technology, and in particular to a cathode material, its preparation method and electrochemical device. Background Technology
[0002] Lithium spinel manganese oxide (LiMn2O4) is abundant, inexpensive, safe, and has a high operating voltage, making it a highly sought-after cathode material for lithium-ion batteries. However, its poor cycle life and high-temperature stability have always hindered its large-scale commercial application.
[0003] There are three main reasons for the performance degradation of spinel lithium manganese oxide: First, during discharge, Mn 3+ Increased concentration triggers the Jahn-Teller effect, causing a transformation of the crystal structure from cubic to tetragonal, thus damaging the lithium-ion insertion / extraction channels; secondly, trace amounts of water in the electrolyte react with lithium salts to generate HF, which corrodes the material surface and induces Mn deposition. 3+ Disproportionation, dissolved Mn 2+ Migration to the negative electrode damages the SEI film, leading to rapid capacity decay; thirdly, at high temperatures, the material surface catalyzes the oxidative decomposition of the electrolyte, forming a high-resistivity surface film, which further reduces the reversible capacity of the electrode.
[0004] Therefore, how to suppress the structural degradation of spinel lithium manganese oxide and the dissolution of Mn while avoiding a significant increase in interfacial impedance and ensuring long-term cycling stability at high temperatures remains a technical challenge to be solved. Summary of the Invention
[0005] In view of this, in order to solve at least one of the above technical problems, this application provides a cathode material.
[0006] In addition, this application also provides a method for preparing the aforementioned cathode material and an electrochemical device using the cathode material.
[0007] In a first aspect, this application provides a cathode material, the cathode material comprising a substrate and a coating layer covering the surface of the substrate; the substrate is lithium manganese oxide doped with Mg, the lithium manganese oxide having a spinel structure, wherein Mg... 2+ Replace part of the Mn in the lithium manganese oxide 3+ Occupying octahedral sites in the spinel structure; the coating layer is lithium vanadium phosphate doped with Mg and Al elements, wherein Mg 2+ Al occupies some of the Li sites in the lithium vanadium phosphate to introduce cation vacancies. 3 + It occupies a portion of the V sites in the lithium vanadium phosphate to form Al-O bonds.
[0008] Based on the first aspect, in some embodiments of this application, the mass of the coating layer accounts for 0.5% to 1.5% of the mass of the substrate.
[0009] Based on the first aspect, in some embodiments of this application, the general formula of the cathode material is [LiMn]. (2-a) Mg a O4]@Li (3-2x) Mg x V (2-y) Al y (PO4)3, where 0.02≤a≤0.04, 0.01≤x≤0.05, 0.01≤y≤0.05, and the [LiMn] (2-a) Mg a O4] is the matrix, and Li (3-2x) Mg x V (2-y) Al y (PO4)3 is the coating layer.
[0010] Based on the first aspect, in some embodiments of this application, the molar ratio of Li, Mn and Mg in the lithium manganese oxide is 1:(1.96~1.98):(0.02~0.04); and / or, in the lithium vanadium phosphate, the molar ratio of Li, Mg, V, Al and P is (2.90~2.98):(0.01~0.05):(1.95~1.99):(0.01~0.05):3.
[0011] Secondly, this application provides a method for preparing a cathode material, the method comprising: mixing a Li source, a Mn source, and a magnesium source to obtain a first mixture; subjecting the first mixture to a single sintering to form lithium manganese oxide with a spinel structure and doped with Mg, wherein, during the single sintering process, Mg... 2+ Replacement part Mn 3+ The matrix is obtained by occupying octahedral sites in the spinel structure; Li source, V source, P source, Mg source, Al source and solvent are mixed to obtain a second mixture; the second mixture is dried and then sintered a second time to form lithium vanadium phosphate doped with Mg and Al elements, wherein, during the second sintering process, Mg... 2+ Occupying a portion of the Li sites in the lithium vanadium phosphate to introduce cation vacancies, and Al 3+ Al-O bonds are generated by occupying some of the V sites in the lithium vanadium phosphate to obtain a coating material; and the substrate and the coating material are mixed and sintered three times to coat the surface of the substrate with the coating material, thereby obtaining the cathode material.
[0012] Based on the second aspect, in some embodiments of this application, the temperature of the first sintering is 750℃~850℃ and the time is 8h~12h; and / or, the temperature of the second sintering is 700℃~800℃ and the time is 6h~15h.
[0013] Based on the second aspect, in some embodiments of this application, the temperature of the three sintering processes is 400℃~600℃, and the time is 4h~8h.
[0014] Based on the second aspect, in some embodiments of this application, the second mixture is dried by spray drying, wherein the spray drying parameters are: air inlet temperature 150℃~180℃, feed speed 500rpm~140rpm, atomization frequency 180Hz~160Hz, and fan frequency 30Hz~55Hz.
[0015] Based on the second aspect, in some embodiments of this application, after the step of drying the second mixture and then performing secondary sintering to form lithium vanadium phosphate doped with Mg and Al elements, the method further includes: a step of sand milling and nano-sizing the sintered product of lithium vanadium phosphate doped with Mg and Al elements, wherein the sand milling and nano-sizing includes: mixing the sintered product with deionized water and sand milling it so that the D50 of the sintered product is 0.1 μm to 0.2 μm, and obtaining a sand milled and nano-sized slurry; drying and pulverizing the sand milled and nano-sized slurry to obtain the coating material.
[0016] Based on the second aspect, in some embodiments of this application, the pulverization includes airflow pulverization, wherein the grading frequency of the airflow pulverization is 30~35Hz, the induced draft frequency is 40~45Hz, and the pulverization is passed through a 200~300 mesh sieve.
[0017] Based on the second aspect, in some embodiments of this application, the mixing of the Li source, Mn source and magnesium source is carried out by dry mixing, the mixing frequency of the dry mixing is 1000Hz~1200Hz and the time is 8min~10min; and / or, the mixing of the matrix and the coating material is carried out by dry mixing, the mixing frequency of the dry mixing is 1200Hz~1400Hz and the mixing time is 10min~30min.
[0018] Thirdly, this application provides an electrochemical device, including a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises a positive electrode material as described above or a positive electrode material prepared by the preparation method described above.
[0019] The cathode material and its preparation method provided in this application suppress the performance degradation of spinel lithium manganese oxide from both bulk and surface levels through the design of the matrix and coating layer. Specifically, Mg doping in the matrix... 2+ Replacement part Mn 3+ It occupies octahedral sites, thereby suppressing the Mn content during charging and discharging to some extent. 3+ The Jahn-Teller distortion induced by concentration changes enhances the structural stability of the spinel framework, while the change in Mn-O bond energy further reduces the Mn dissolution rate. Based on this, the coating physically isolates the substrate surface from the electrolyte, thereby reducing HF erosion of the substrate surface. Simultaneously, lithium vanadium phosphate itself can reversibly intercalate and deintercalate lithium ions within a voltage window of 3.0V–4.3V, thus maintaining lithium ion transport efficiency at the interface and keeping the interfacial impedance at a low level. Furthermore, the Mg in the coating... 2+ And Al 3+ The introduction of this material enhances the structural stability of lithium vanadium phosphate, thereby helping the coating layer maintain its structural integrity and continue to play its protective role during long-term charge and discharge processes.
[0020] Therefore, the high-temperature capacity retention and long-term cycle stability of this cathode material are improved, effectively alleviating the performance degradation problem of spinel lithium manganese oxide caused by the Jahn-Teller effect, Mn dissolution and increased interfacial impedance. Attached Figure Description
[0021] Figure 1 This is a flowchart of the preparation process of the cathode material in Example 1 of this application.
[0022] Figure 2 This is a SEM image of the uncoated Mg-doped lithium manganese oxide matrix material in Comparative Example 2 of this application.
[0023] Figure 3 This is a SEM image of the Mg-Al double-doped lithium vanadium phosphate coating material in Example 1 of this application.
[0024] Figure 4 This is a SEM image of the lithium manganese oxide cathode material modified with active coating of lithium vanadium phosphate in Example 1 of this application. Detailed Implementation
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the embodiments of this application pertain. The terminology used herein is for the purpose of describing particular implementations only and is not intended to limit the embodiments of this application. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0026] The following describes some embodiments of this application in detail. Unless otherwise specified, the embodiments and features described below can be combined with each other.
[0027] Currently, spinel lithium manganese oxide suffers from poor cycle life and high-temperature stability. To address this issue, researchers have explored various modification schemes. The first is bulk doping, which introduces elements such as Al and Mg to suppress the Jahn-Teller effect. However, this cannot completely prevent direct contact between the electrolyte and the active material surface, limiting its effectiveness in inhibiting Mn dissolution. The second is surface coating, which coats lithium manganese oxide particles with inert oxides for physical isolation. However, these inactive materials hinder lithium ion passage through the interface, sacrificing rate performance. Recent studies have proposed coating lithium manganese oxide with lithium vanadium phosphate and adding a carbon layer between the two to improve the interface. However, this double-layer structure increases process complexity, and the carbon layer itself may trigger side reactions during high-temperature sintering.
[0028] For this purpose, please see Figure 1 This application provides a method for preparing a cathode material, the method comprising the following steps: Step S1: Mix the Li source, Mn source and magnesium source to obtain the first mixture.
[0029] Step S2: The first mixture is sintered once to form lithium manganese oxide with a spinel structure and doped with Mg, wherein Mg is doped during the first sintering process. 2+ Replacement part Mn 3+ The matrix is obtained by occupying the octahedral sites in the spinel structure.
[0030] In step S1, a dry mixing process is used to disperse the raw material components, which helps to make the Li source, Mn source and Mg source mix uniformly under mechanical force, so that the first mixture has good component consistency, which in turn provides favorable conditions for the full occurrence of solid phase reaction in the subsequent sintering process, thereby improving the phase uniformity of the matrix material.
[0031] In step S2, a one-step sintering method is used to simultaneously synthesize spinel lithium manganese oxide and dope Mg, which simplifies the preparation process (eliminating the need for additional doping steps), while Mg... 2+ During sintering, it enters the spinel lattice in situ and occupies octahedral sites, thereby enabling Mg... 2+ The bond with the matrix framework is relatively strong, thereby enhancing the stability of the spinel structure, and consequently, due to the partial Mn... 3+ Mg 2+ The substitution reduces the degree of structural distortion during charging and discharging, thereby improving the structural reversibility of the matrix.
[0032] In some embodiments, in step S1, the Li source, Mn source, and Mg source are mixed using a dry mixing method. The mixing frequency during dry mixing is 1000Hz~1400Hz, and the mixing time is 8min~10min. Using a dry mixing method facilitates the uniform dispersion of each component without introducing solvents, thus eliminating the need for subsequent drying steps and simplifying the preparation process. Furthermore, the absence of solvents ensures the purity of the matrix material, which in turn facilitates the full execution of the solid-state reaction during the single sintering process. This improves the integrity of the crystal structure and batch consistency of the matrix material.
[0033] In some embodiments, the molar ratio of Li in the Li source, Mn in the Mn source, and Mg in the Mg source in step S1 is 1:(1.96~1.98):(0.02~0.04). By controlling the molar ratio of Li, Mn, and Mg within the above range in step S1, the proportional relationship between Mg and Mn is harmonized, and Mg... 2+ It can effectively replace part of Mn 3+ It occupies octahedral sites, thereby enhancing the stability of the spinel framework, while Mn 3+ The reduction in concentration effectively controlled the Jahn-Teller distortion, resulting in better structural reversibility of the matrix during charge and discharge, and thus improved cycle stability.
[0034] In some embodiments, the Li element is added in the form of lithium carbonate in step S1, but it is not limited to this. Using lithium carbonate as the lithium source is beneficial to improving the mixing uniformity of lithium carbonate with manganese and magnesium sources, and the decomposition temperature of lithium carbonate in the subsequent sintering process is more suitable, allowing the solid-phase reaction to proceed fully, thereby making the crystal development of the matrix material more complete.
[0035] In some embodiments, the Mn element in step S1 is added in the form of manganese tetroxide, but is not limited thereto. Using manganese tetroxide as the manganese source is advantageous because the Mn in manganese tetroxide exists in a mixed +2 and +3 valence state, which interacts with the Mn in spinel lithium manganese oxide. 3 + / Mn 4+ The valence states of manganese tetroxide are relatively similar, which is conducive to the formation of a complete spinel phase during sintering. At the same time, the particle morphology and particle size distribution of manganese tetroxide are relatively regular, and the uniformity of mixing and the structural consistency of sintered products are improved.
[0036] In some embodiments, Mg is added in step S1 in the form of magnesium oxide, but this is not limited to this. Magnesium oxide is used as the magnesium source because it has a low impurity content and good lattice matching with the lithium manganese oxide matrix. 2+During the sintering process, it can relatively easily enter the octahedral sites in the spinel lattice, thereby achieving the desired Mn content. 3+ An effective alternative is provided, thus ensuring the doping effect of the matrix.
[0037] In some embodiments, the sintering temperature in step S2 is 750°C to 850°C, and the time is 8 hours to 12 hours. Using this temperature range for sintering is beneficial for Mg… 2+ Sufficient migration energy is obtained to smoothly enter the spinel lattice and occupy octahedral sites. Simultaneously, the solid-state reaction can proceed fully to ensure complete spinel structure development and a relatively uniform grain size distribution. The doping effect and structural integrity of the matrix are both guaranteed, thereby improving the electrochemical performance of the matrix. The sintering temperature can, for example, be 750℃, 770℃, 800℃, 820℃, 850℃, or any value within the range of any two of the above values. The sintering time can, for example, be 8h, 9h, 10h, 11h, 12h, or any value within the range of any two of the above values.
[0038] In some embodiments, the general formula of the resulting matrix is LiMn. (2-a) Mg a O4, where 0.02 ≤ a ≤ 0.04. The matrix formula obtained in step S2 is shown above. When the value of a is controlled within the above range, Mg 2+ For Mn 3+ The substitution amount is moderate, the lattice volume change of the spinel framework is small during the charge and discharge process, the structural reversibility is good, and the overall capacity performance of the material is not significantly affected. Thus, the cycle stability and capacity performance of the matrix are balanced.
[0039] Step S3: Mix the Li source, V source, P source, Mg source, Al source with the solvent to obtain the second mixture.
[0040] Step S4: After drying the second mixture, it is subjected to secondary sintering to form lithium vanadium phosphate doped with Mg and Al elements. During the secondary sintering process, Mg... 2+ Occupying some Li sites in lithium vanadium phosphate to introduce cation vacancies, and Al 3+ Al-O bonds are formed by occupying some of the V sites in lithium vanadium phosphate to obtain the coating material.
[0041] In step S3, the Li source, V source, P source, Mg source and Al source are mixed with the solvent by liquid phase mixing, so that each raw material component can be fully dispersed, thereby achieving a high degree of uniformity in the distribution of each element in the second mixture. Based on this, favorable conditions are obtained for the synthesis of lithium vanadium phosphate and the uniform distribution of Mg and Al dopants in the crystal lattice during the subsequent sintering process.
[0042] In step S4, the second mixture is dried and then directly subjected to secondary sintering, thus simultaneously achieving Mg synthesis during the synthesis of lithium vanadium phosphate. 2+ And Al 3+ In-situ doping eliminates the need for pre-synthesizing lithium vanadium phosphate followed by additional doping treatment, thus avoiding impurities and phase inhomogeneities that may be introduced in multi-step processes, and making the preparation process more streamlined; among which Mg 2+ During sintering, Li sites enter the lithium vanadium phosphate, introducing cation vacancies into the crystal lattice. + The migration activation energy in the three-dimensional channels of the coating layer is thus reduced, and the diffusion capacity is enhanced, which helps to maintain a low ion transport impedance at the interface between the coating layer and the matrix; Al 3+ It simultaneously enters the V site and forms an Al-O bond with oxygen, thus pinning the NASICON-type framework of lithium vanadium phosphate. During charge-discharge cycles, due to V 3+ / V 4+ The lattice volume change induced by redox reaction is effectively suppressed, thereby enhancing the structural stability of the coating layer. The synergistic effect of the two doping methods enables the coating layer material to possess both improved ion conductivity and high structural stability. When used as a coating layer on the substrate surface, it can physically isolate the substrate from the electrolyte to reduce the erosion of the substrate by HF, without causing a significant increase in interfacial impedance due to the coating layer itself not participating in the electrochemical reaction. At the same time, the entire preparation process does not require the addition of a carbon layer, which is much simpler than existing double-layer coating structures.
[0043] In some embodiments, in step S3, the solvent includes deionized water. Using deionized water as the solvent ensures the purity of the coating material due to its low impurity content. Simultaneously, deionized water exhibits good wettability with each raw material component, enabling uniform dispersion of each component in the liquid phase.
[0044] In some embodiments, in step S3, the molar ratio of Li element in the Li source, Mg element in the Mg source, V element in the V source, Al element in the Al source, and P element in the P source is (2.90~2.98):(0.01~0.05):(1.95~1.99):(0.01~0.05):3.
[0045] In this step, the molar ratios of each element are controlled within the aforementioned range, thus harmonizing the proportions of Mg to Li and Al to V, and ensuring the integrity of the Mg content in the coating layer. 2+ The substitution amount at the Li site is moderate, and the introduction amount of cation vacancies is suitable. + The migration capability is thus improved; at the same time, AI 3+With a moderate substitution amount at the V-site, the Al-O bonds effectively pinnate the framework, thereby enhancing the structural stability of the coating layer. In some embodiments, Li is added in step S3 in the form of lithium dihydrogen phosphate. Lithium dihydrogen phosphate serves as both a lithium source and a phosphorus source, exhibiting good compatibility with vanadium and dopant sources in the liquid phase system. This facilitates uniform mixing of the components at the molecular level, thus improving the phase uniformity of the coating layer material.
[0046] In some embodiments, V is added in step S3 in the form of vanadium pentoxide. The V in vanadium pentoxide is in the +5 valence state, which is reduced to the +3 valence state during subsequent sintering and enters the V sites in the lithium vanadium phosphate lattice. This process is accompanied by volume shrinkage and lattice densification, which is beneficial for forming a structurally complete lithium vanadium phosphate phase, thereby improving the crystallinity of the coating material.
[0047] In some embodiments, in step S3, the phosphorus element is added in the form of lithium dihydrogen phosphate and phosphoric acid. Lithium dihydrogen phosphate serves as both a lithium source and a partial phosphorus source, while the additional phosphoric acid is used to adjust the stoichiometric ratio of phosphorus, ensuring that the total phosphorus content accurately meets the stoichiometric ratio requirements. This guarantees the phase purity and structural consistency of the coating material.
[0048] In some embodiments, Mg is added in step S3 in the form of magnesium carbonate. Magnesium carbonate has good dispersibility in the liquid phase system, and its decomposition products are magnesium oxide and carbon dioxide, leaving few impurities after decomposition, which helps to ensure the purity of the coating material. Meanwhile, Mg... 2+ During the sintering process, it can smoothly enter the Li sites in the lithium vanadium phosphate lattice, thus ensuring the doping effect.
[0049] In some embodiments, Al is added in the form of alumina in step S3. Alumina has good chemical stability, is less prone to side reactions in the liquid phase system, and Al is added during subsequent sintering. 3+ It can enter the V site in the lithium vanadium phosphate lattice relatively smoothly and form Al-O bonds with oxygen, thereby improving the structural stability of the coating layer.
[0050] In some embodiments, step S4, before drying the second mixture, further includes: grinding the second mixture in a sand mill until the particle size D50 in the slurry is ≤0.5μm, and then drying the resulting slurry. After grinding the second mixture, the particle size of each raw material component is relatively small and uniformly distributed, increasing the contact area for the solid-phase reaction. This allows for the uniform distribution of dopant elements in the lithium vanadium phosphate lattice, thereby improving the phase consistency of the coating material. The median particle size D50 after grinding can, for example, be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, or any value within the range of any two of the above values.
[0051] In some embodiments, in step S4, the slurry after sand milling is dried by spray drying. The spray drying parameters are as follows: inlet air temperature 150℃~180℃, feed speed 500rpm~140rpm, atomization frequency 180Hz~160Hz, and fan frequency 30Hz~55Hz. Spray drying of the slurry after sand milling allows it to rapidly transform into a powder precursor under the action of the atomizer and hot air. This prevents the precursor particles from agglomerating, and the resulting precursor particles have a more regular morphology and lower moisture content, which is beneficial for more sufficient contact between the components during the subsequent secondary sintering process.
[0052] In some embodiments, the secondary sintering temperature in step S4 is 700℃~800℃, and the time is 6h~15h. When carried out within the above temperature and time range, the synthesis reaction of lithium vanadium phosphate can proceed sufficiently, and Mg... 2+ And Al 3+ Sufficient migration energy is obtained during this process, allowing the material to enter the Li and V sites respectively. This results in a more complete crystal structure development of the coating material, enhancing both ion conductivity and structural stability. The secondary sintering temperature can be, for example, 700℃, 720℃, 750℃, 780℃, 800℃, or any value within the range of any two of the above values; the secondary sintering time can be, for example, 6h, 8h, 10h, 12h, 15h, or any value within the range of any two of the above values.
[0053] In some embodiments, after the step S4 of drying the second mixture and then performing a secondary sintering to form lithium vanadium phosphate doped with Mg and Al elements, the method further includes a step of sand milling and nano-sizing the sintered product of lithium vanadium phosphate doped with Mg and Al elements. Specifically, the sand milling and nano-sizing includes: Step 1: Mix the sintered product with deionized water at a solid-liquid ratio of 1:3, and then perform sand milling to nano-size the sintered product particles so that the D50 of the particles is 0.1μm~0.2μm, and obtain a slurry that has been sand milled and nano-sized.
[0054] In this step, the sintered product after secondary sintering is mixed with deionized water at a solid-liquid ratio of 1:3 and then subjected to sand milling for nano-sizing. The sintered product is subjected to mechanical grinding in the liquid medium, which further refines the particle size and makes the distribution more uniform. This is beneficial for the coating material to adhere more uniformly to the surface of the matrix particles when it is mixed with the matrix in the subsequent process, thereby improving the coverage integrity and interface uniformity of the coating.
[0055] Step 2: The nano-sized slurry is dried and pulverized to obtain the coating material. In this step, the nano-sized slurry is dried to remove moisture and obtain a dried powder. The dried powder is then pulverized to effectively dissociate the soft agglomerates generated during the drying process. The resulting coating material has a more uniform particle size and better dispersibility.
[0056] In some embodiments, the drying parameters in step 2 are as follows: vacuum drying, drying temperature of 120℃~130℃, and time of 8~10h. Using vacuum drying in this step to dry the slurry after sand milling and nano-sizing is beneficial for fully removing moisture from the slurry at a lower temperature and inhibiting abnormal particle growth. The particle size distribution and dispersibility of the powder obtained after drying are well maintained.
[0057] In some embodiments, the pulverization in step 2 includes air jet milling, with a classification frequency of 30Hz~35Hz and an induced draft frequency of 40Hz~45Hz, followed by sieving through a 200-300 mesh sieve. In this step, air jet milling is used to process and sieve the dried powder. Aggregates in the powder are effectively dissociated under the action of the airflow. Simultaneously, the sieving operation results in a more concentrated particle size distribution of the obtained powder, which is beneficial for the uniform spreading and complete coverage of the coating material on the substrate surface, thereby improving the interfacial contact quality.
[0058] In some embodiments, the general formula of the coating material obtained in step S4 is Li (3-2x) Mg x V (2-y) Al y (PO4)3, where 0.01≤x≤0.05, 0.01≤y≤0.05. When the values of x and y are controlled within the above ranges, Mg 2+ A moderate substitution amount at the Li site is beneficial for introducing an appropriate amount of cation vacancies to enhance the ion conductivity of the coating layer; Al 3+A moderate amount of substitution at the V site is beneficial for the stable pinning effect on the framework structure through Al-O bonds, thereby improving the ionic conductivity and structural stability of the coating material.
[0059] Step S5: Mix the substrate and the coating material, and sinter three times to coat the substrate surface with the coating material, thereby generating a substrate coated with the coating, which is the positive electrode material.
[0060] The general formula for cathode materials is [LiMn] (2-a) Mg a O4]@Li (3-2x) Mg x V (2-y) Al y (PO4)3, where 0.02≤a≤0.04, 0.01≤x≤0.05, 0.01≤y≤0.05, [LiMn (2-a) Mg a O4] is the matrix, Li (3-2x) Mg x V (2-y) Al y (PO4)3 is the coating layer.
[0061] In step S5, under the heat treatment of three sintering processes, the coating material undergoes an interfacial reaction with the substrate surface and forms a bond, thus firmly adhering to the surface of the substrate particles. The resulting core-shell structure effectively blocks direct contact between the substrate and the electrolyte, while the electrochemical activity of the coating itself is preserved, and lithium-ion transport at the interface is not significantly hindered. As a result, the performance degradation problems caused by spinel structure distortion, Mn dissolution, and interfacial polarization are effectively improved.
[0062] In some embodiments, in step S5, the matrix and coating material are dry-mixed at a mixing frequency of 1200Hz to 1400Hz for a mixing time of 10 to 30 minutes. Using a dry mixing method in step S5, and controlling the mixing parameters within the aforementioned range, facilitates uniform adhesion of the matrix and coating material under mechanical force, resulting in a more complete coverage of the matrix particles by the coating material. Furthermore, dry mixing avoids the adverse effects of solvent residue on interfacial bonding, thereby improving the interfacial bonding strength between the coating and the matrix.
[0063] In some embodiments, the temperature of the three sintering processes in step S5 is 400°C to 600°C, and the time is 4 hours to 8 hours. During the three sintering processes in step S5, as the temperature gradually increases, physical adsorption, surface activation, and interfacial reactions occur sequentially between the coating material and the substrate, thereby gradually establishing an interfacial bond from weak to strong. In the heating stage below 400°C, the coating particles adhere to the surface of the substrate particles through van der Waals forces and electrostatic adsorption. When the temperature rises to 300°C to 400°C, the suspended hydroxyl groups of Mn-OH on the substrate surface begin to undergo dehydration condensation, and the P-OH and VO end groups on the coating surface gradually activate, thus creating conditions for subsequent interfacial chemical reactions. When the temperature further rises to 400°C to 600°C, on the one hand, the PO4 tetrahedral terminal oxygen in the coating layer forms PO-Mn coordination bonds with the Mn ions on the substrate surface as Lewis acids. At the same time, the nitrogen atmosphere effectively inhibits the excessive oxidation of Mn on the substrate surface, allowing Mn to... 2+ / Mn 3+ The active sites for coordination are retained, which is conducive to the formation of the aforementioned coordination bonds. On the other hand, the coating particles and the matrix form sintering necks through surface diffusion, achieving mechanical interlocking. Under the synergistic effect of the aforementioned physical adsorption, chemical bonding, and mechanical interlocking, the coating layer is firmly attached to the surface of the matrix particles, thereby ensuring sufficient interfacial bonding strength. At the same time, this temperature range is beneficial to maintaining the stability of the spinel structure of the matrix, thereby improving the coverage integrity and interfacial bonding strength of the coating layer. The tertiary sintering temperature can be, for example, 400℃, 450℃, 500℃, 550℃, 600℃, or any value within the range of any two of the above values. The tertiary sintering time can be, for example, 4h, 5h, 6h, 7h, 8h, or any value within the range of any two of the above values.
[0064] In some embodiments, the mass of the coating layer is 0.5% to 1.5% of the substrate mass. Within this range, the coating layer can relatively completely cover the substrate surface, thereby forming an effective physical isolation layer to prevent the electrolyte from corroding the substrate. At the same time, this mass ratio helps to maintain a moderate coating layer thickness, ensuring a relatively unobstructed lithium-ion transport path at the interface, thus guaranteeing the capacity utilization and rate performance of the substrate. The protective effect of the coating layer and the interfacial conductivity are thus balanced. The percentage of the coating layer mass to the substrate mass can, for example, be 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, or any value within the range of any two of the above values.
[0065] This application also provides a cathode material, which includes a substrate and a coating layer covering the surface of the substrate; the substrate is lithium manganese oxide doped with Mg, and the lithium manganese oxide has a spinel structure, wherein Mg... 2+ Replacing part of the Mn in lithium manganese oxide3+ It occupies octahedral sites in the spinel structure; the coating layer is lithium vanadium phosphate doped with Mg and Al elements, wherein Mg 2+ Al occupies some of the Li sites in lithium vanadium phosphate to introduce cation vacancies. 3+ It occupies some of the V sites in lithium vanadium phosphate to form Al-O bonds.
[0066] Mg doped in the matrix 2+ Replacement part Mn 3+ It occupies octahedral sites in the spinel structure, thus stabilizing the spinel framework. During charging and discharging, due to Mn 3+ Structural distortions caused by concentration changes are thus suppressed, improving the structural reversibility of the matrix during cycling and slowing down the Mn dissolution rate. Furthermore, the lithium vanadium phosphate coating on the matrix surface physically isolates the matrix from the electrolyte, reducing direct erosion of the matrix surface by the electrolyte. Simultaneously, lithium vanadium phosphate itself can reversibly insert and extract lithium ions within a voltage window of 3.0V–4.3V, maintaining lithium ion transport at the interface and effectively controlling the interfacial impedance. Mg doping in the coating layer... 2+ Occupying Li sites in lithium vanadium phosphate and introducing cation vacancies, thereby reducing Li + The migration activation energy is increased, thereby enhancing the lithium-ion conductivity at the interface; doped Al 3+ Occupying the V sites in lithium vanadium phosphate and forming Al-O bonds with oxygen, the coating layer stabilizes the skeletal structure of lithium vanadium phosphate, thus ensuring the structural integrity of the coating layer during long-term charge-discharge processes. Based on the synergistic effect of the substrate and the coating layer, the cycle stability and capacity retention of this cathode material at high temperatures are improved.
[0067] Compared with related technologies, the cathode material and preparation method provided in this application have the following advantages: 1. The matrix is magnesium-doped spinel lithium manganese oxide, wherein Mg 2+ Replacement part Mn 3+ And occupying octahedral sites, the stability of the spinel framework is enhanced, and during charging and discharging, due to Mn 3+ The structural distortion caused by concentration changes was suppressed, the dissolution rate of Mn was reduced, and the structural reversibility and cycling stability of the matrix were improved.
[0068] 2. The coating layer is magnesium-aluminum dual-doped lithium vanadium phosphate. This coating layer physically isolates the substrate surface from the electrolyte, reducing the corrosion of the substrate by HF. At the same time, lithium vanadium phosphate itself can reversibly insert and extract lithium ions within a voltage window of 3.0V~4.3V, so lithium ion transport at the interface is maintained and the interface impedance is kept at a low level.
[0069] 3. Mg doped in the coating layer 2+ Occupying Li sites and introducing cation vacancies, Li + The migration activation energy is thus reduced, and the lithium-ion conductivity at the interface is improved; doped Al 3+ By occupying V sites and forming Al-O bonds with oxygen, the framework structure of lithium vanadium phosphate is stabilized, and the structural integrity of the coating layer is maintained during long-term cycling.
[0070] 4. Compared with the existing double-layer structure that requires a carbon coating layer between lithium vanadium phosphate and lithium manganese oxide, this application does not require a carbon layer, which simplifies the preparation process and avoids side reactions that may be caused by the carbon layer during high-temperature sintering.
[0071] This application also provides an electrochemical device, including a positive electrode, a negative electrode, and an electrolyte disposed between the positive and negative electrodes. The positive electrode includes a positive electrode material as described above or a positive electrode material prepared by the aforementioned preparation method. Because this electrochemical device includes the positive electrode material provided in this application, its cycle life, rate performance, and high-temperature stability are all improved.
[0072] The present application will be further described below with reference to specific embodiments and comparative examples.
[0073] Example 1 Step 1: Preparation of magnesium-doped lithium manganese oxide matrix material Step (1.1) Preparation of the first mixture: Lithium carbonate, manganese tetroxide and magnesium oxide are mixed in a molar ratio of Li:Mn:Mg=1:1.97:0.03. The above raw materials are mixed by dry mixing to obtain the first mixture.
[0074] Step (1.2), First sintering: The first mixture is placed in an air atmosphere and sintered at 800℃ for 12 hours. After natural cooling, it is pulverized by airflow. The pulverization frequency is 10Hz, the induced draft frequency is 40Hz, and it is passed through a 400-mesh sieve to obtain the chemical formula LiMn. (1.97) Mg (0.03) O4 magnesium-doped lithium manganese oxide matrix material.
[0075] Step 2: Preparation of magnesium-aluminum dual-doped lithium vanadium phosphate coating material Step (2.1), Preparation of the second mixture: Lithium dihydrogen phosphate, magnesium carbonate, vanadium pentoxide, alumina, and phosphoric acid were mixed with deionized water at a molar ratio of Li:Mg:V:Al:P = 2.94:0.03:1.97:0.03:3, with a solid-liquid ratio of 1:2. The mixture was then fed into a sand mill for sand milling until the particle size D50 of the slurry was ≤0.5μm. The resulting slurry was then spray-dried at an inlet air temperature of 165℃, a feed rate of 90rpm, an atomization frequency of 230Hz, and a fan frequency of 50Hz to obtain precursor powder.
[0076] Step (2.2), Secondary sintering: The precursor powder is placed in a tube furnace and sintered at 750°C for 10 hours under nitrogen atmosphere protection, and then naturally cooled.
[0077] Step (2.3), Post-processing: The sintered product obtained in step (2.2) was mixed with deionized water at a solid-liquid ratio of 1:3 and subjected to secondary sand milling to nano-scale processing until the particle size D50 ≤ 0.2 μm. The resulting nano-slurry was placed in a vacuum oven and dried at 120℃ for 10 h. The dried product was then subjected to air jet milling with a classification frequency of 30 Hz and an induced draft frequency of 45 Hz, and passed through a 500-mesh sieve to obtain the chemical formula Li. 2.94 Mg 0.03 V 1.97 Al 0.03 (PO4)3 coating material.
[0078] Step 3: Active coating and final sintering Step (3.1), Mixing: According to the ratio of the coating material to the total mass of the matrix material, the matrix material obtained in step one and the coating material obtained in step two are put into a high-speed mixer for dry mixing. The mixing frequency is 1400Hz and the mixing time is 30min to obtain the coating precursor.
[0079] Step (3.2), three-stage sintering: The coated precursor is placed under nitrogen atmosphere protection and sintered at 500℃ for 6 hours. After natural cooling, it is mechanically crushed and passed through a 400-mesh sieve to obtain the cathode material.
[0080] Example 2 The difference between this embodiment and embodiment 1 is that the coating material in step (3.1) accounts for 0.5% of the total mass of the matrix material, while the rest remains the same as in embodiment 1.
[0081] Example 3 The difference between this embodiment and embodiment 1 is that the coating material in step (3.1) accounts for 1.5% of the total mass of the matrix material, while the rest remains the same as in embodiment 1.
[0082] Comparative Example 1 The difference between this embodiment and Embodiment 1 is that the matrix material is not Mg-doped (magnesium oxide is not added in step one) and there is no coating layer (steps two and three are omitted), while the rest is consistent with Embodiment 1.
[0083] Comparative Example 2 The difference between this embodiment and Embodiment 1 is that there is no coating layer (steps two and three are omitted), the matrix material is prepared according to step one to obtain Mg-doped lithium manganese oxide material, and the rest is consistent with Embodiment 1.
[0084] Comparative Example 3 The difference between this embodiment and Embodiment 1 is that: in step 2.1, magnesium carbonate and aluminum oxide are not added, resulting in an undoped lithium vanadium phosphate coating material; the remaining steps are the same as in Embodiment 1, and the rest of the parts are consistent with Embodiment 1.
[0085] The differences between Examples 2 and 3 and Comparative Examples 1 and 3 are shown in Table 1 below.
[0086] Table 1 Characterization of the structure and morphology of the cathode material: The microstructure of the cathode material was observed using a scanning electron microscope, and SEM images were recorded.
[0087] Preparation of positive electrode sheet: The positive electrode material obtained above is mixed with conductive carbon black (SuperP) and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1. An appropriate amount of N-methylpyrrolidone (NMP) is added and stirred to form a uniform slurry. The slurry is coated on an aluminum foil current collector and then dried, rolled, and cut to form a positive electrode sheet.
[0088] Preparation of negative electrode sheet: Artificial graphite is used as the negative electrode active material. It is mixed with conductive carbon black, styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) in a mass ratio of 94:1:2.5:2.5 to form a slurry. The slurry is then coated onto a copper foil current collector to form a negative electrode sheet.
[0089] Preparation of pouch battery: The above positive electrode, negative electrode and polyolefin porous membrane are assembled into a cell, injected with carbonate electrolyte with LiPF6 as lithium salt, and after encapsulation, formation, aging and capacity testing, a pouch battery with a rated capacity of 2Ah is obtained.
[0090] 1 / 3C Discharge Capacity Test: The pouch battery was placed in a constant temperature chamber at 25℃±2℃ and left to stand for 30 minutes. Then, it was charged at a constant current of 1 / 3C to 4.3V, followed by constant voltage charging until the current dropped to 0.05C. After standing for 10 minutes, it was discharged at a constant current of 1 / 3C to 3.0V, and the discharge capacity was recorded. This charging and discharging process was repeated three times, and the discharge capacity of the third discharge was taken as the 1 / 3C discharge capacity.
[0091] 2C discharge capacity test: Place the soft pack battery in a constant temperature chamber at 25℃±2℃ and let it stand for 30 minutes. Then charge the soft pack battery with a constant current of 1 / 3C until the charging cutoff voltage is 4.3V. Then charge it with a constant voltage until the current drops to 0.05C and stop charging. After standing for 10 minutes, discharge it with a constant current of 2C until the discharge cutoff voltage is 3.0V. Record the 2C discharge capacity and calculate the 2C discharge capacity retention rate according to the formula: 2C discharge capacity retention rate (%) = (2C discharge capacity / 1 / 3C discharge capacity) × 100%.
[0092] The evaluation index of 2C discharge capacity is as follows: record the 2C discharge capacity and the 2C discharge capacity retention rate. The higher the value, the better the rate performance of the material.
[0093] High-temperature cycle performance test: The pouch battery was placed in a 45℃±1℃ high-temperature constant temperature chamber and left to stand for 30 minutes to allow the battery to reach a constant temperature. Then, under the condition of 45℃±1℃, the pouch battery was charged with a constant current of 1C to 4.3V, and then charged with a constant voltage until the current dropped to 0.05C. After standing for 10 minutes, it was discharged with a constant current of 1C to 3.0V, and the initial discharge capacity C0 was recorded. The above charge-discharge cycle was repeated, and the discharge capacity C was recorded after every 50 cycles. n And according to the formula "Capacity retention rate (%) = (C n Calculate the capacity retention rate using " / C0)×100%" and continue the cycle until the capacity retention rate decays to 80% of the initial capacity. Record the number of cycles at this point.
[0094] 1C charge-1C discharge high-temperature cycling at 45℃ @ 80% retention rate test: The testing equipment included a lithium-ion battery electrochemical performance tester and a high-temperature constant temperature chamber (45℃±1℃). The specific test steps are as follows: (1) Place the soft-pack battery in a high-temperature constant temperature chamber at 45℃±1℃ and let it stand for 30 minutes to allow the battery to reach a constant temperature. (2) Charge at a constant current of 1C until the charging cutoff voltage is reached, and then charge at a constant voltage until the current drops to 0.05C and charging is stopped. (3) Let stand for 10 minutes; (4) Discharge at a constant current of 1C until the discharge cutoff voltage, and record the first discharge capacity C0; (5) Repeat steps (2) to (4) to perform continuous charge and discharge cycles; (6) Record the discharge capacity C after every 50 cycles. n Calculate the capacity retention rate using the following formula: Capacity retention rate (%) = (C n / C0)×100%.
[0095] (7) Continue the cycle until the capacity retention rate decays to 80% of the initial capacity, and record the number of cycles at this point.
[0096] Evaluation metric: Record the number of cycles required for the capacity retention rate to decay to 80%. The higher the number of cycles, the better the high-temperature cycle life of the material.
[0097] 7-day capacity retention test at 55℃ & 100% SOC: The testing equipment included a lithium-ion battery electrochemical performance tester and a high-temperature constant temperature chamber (55℃±1℃). The test procedures are as follows: (1) Under normal temperature conditions of 25℃±2℃, the soft pack battery is charged at a constant current of 1 / 3C to the charging cutoff voltage, and then charged at a constant voltage until the current drops to 0.05C, so that the battery reaches 100% SOC (state of charge). (2) Let stand for 30 minutes, then discharge at a constant current of 1 / 3C until the discharge cutoff voltage, and record the initial discharge capacity C0; (3) Charge the battery again to 100% SOC in the same way; (4) Place the fully charged battery in a high-temperature constant temperature chamber at 55℃±1℃ and leave it open for 7 days (168h). (5) Remove the battery and allow it to recover in an environment of 25℃±2℃ for 2~4 hours; (6) Discharge at a constant current of 1 / 3C until the discharge cutoff voltage, and record the remaining discharge capacity C1 after resting; (7) Calculate the 7-day high-temperature capacity retention rate according to the following formula: Capacity retention rate (%) = (C1 / C0) × 100%.
[0098] Evaluation index: Record the capacity retention rate after 7 days of storage at 55℃ and 100% SOC. The higher the value, the better the high-temperature storage performance of the material.
[0099] The experimental test results of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 2 below.
[0100] Table 2 Results Analysis: Analysis of the Effect of Mg Doping on the Matrix: Combined with Figure 2 The SEM images shown indicate that the Mg-doped lithium manganese oxide matrix in Comparative Example 2 is uncoated, exhibiting a single-crystal morphology and a smooth surface. Comparing Comparative Example 1 and Comparative Example 2, the 1 / 3C discharge capacity of Comparative Example 2 after Mg doping is 105.5 mAh / g, which is essentially the same as the 105.4 mAh / g of Comparative Example 1, indicating that Mg... 2+ Replace part of Mn 3+The change in position did not negatively impact the material's reversible capacity. In terms of rate performance, the 2C capacity retention improved from 92.5% to 93.5%; in terms of high-temperature performance, the number of cycles at 45°C with 1C / 1C to 80% capacity retention increased from 342 to 397, and the capacity retention after 7 days at 55°C and 100% SOC improved from 83.5% to 85.1%.
[0101] The above results indicate that Mg doping stabilizes the spinel [MnO6] octahedral framework through the "pillar effect," effectively suppressing Jahn-Teller lattice distortion and Mn dissolution, thereby improving the high-temperature cycling stability and storage performance of the material. However, the improvement in rate performance is relatively limited because Mg doping mainly affects the stability of the bulk structure and fails to physically isolate the direct contact between the electrolyte and the surface of the active material. The catalytic activity of surface Mn and the problem of HF erosion still exist.
[0102] Analysis of the effect of undoped LVP coating: Comparing Comparative Example 2 and Comparative Example 3, it can be seen that after Comparative Example 3 coated the surface of the Mg-doped substrate with 1.0% undoped lithium vanadium phosphate (Li3V2(PO4)3), the 1 / 3C discharge capacity increased from 105.5 mAh / g to 108.5 mAh / g, the 2C capacity retention increased from 93.5% to 96.1%, the number of cycles to 80% at 45℃ increased from 397 to 457, and the high-temperature storage capacity retention increased from 85.1% to 88.2%. These results indicate that the LVP coating layer, as a physical isolation layer, effectively reduces the erosion of the lithium manganese oxide surface by HF and the MnO2 content. 3+ The disproportionation and dissolution of LVP, while LVP itself can participate in Li within a voltage window of 3.0~4.3V. + The reversible insertion / extraction of LVP serves as both a "protective layer" and an "active buffer layer," thus improving rate performance and high-temperature durability without sacrificing capacity. However, undoped LVP has extremely low intrinsic electronic conductivity (approximately 10⁻⁶). -8 The S / cm level still limits the further development of rate performance to some extent, and its structural stability still has room for improvement under long-term cycling and high-temperature storage conditions.
[0103] Synergistic effect analysis of Mg-Al dual-doped LVP coating: combined with Figure 3 The SEM images of the doped lithium vanadium phosphate shown reveal that the coating material particles are nanoscale and well-dispersed, which is beneficial for achieving uniform coating on the substrate surface. Comparison of Comparative Example 3 with Examples 1-3 shows that the use of Mg-Al dual-doped LVP (Li 2.94 Mg 0.03 V 1.97 Al 0.03 After replacing undoped LVP with (PO4)3 as the coating layer, the various properties were further improved.
[0104] Regarding capacity performance, the 1 / 3C discharge capacity of Examples 1-3 was 108.9-109.8 mAh / g, all higher than that of Comparative Example 3 (108.5 mAh / g), indicating that Mg... 2+ Li sites are occupied to introduce lithium vacancies and Al 3+ The dual-doping strategy, which occupies the V-site stable framework, did not introduce non-electrochemically active Mg. 2+ And Al 3+ However, sacrificing the reversible capacity of the material actually improves the utilization rate of the active material due to the increased ionic conductivity of the coating layer.
[0105] Regarding rate performance, the 2C capacity retention rates of Examples 1-3 reached 98.3%-98.9%, an improvement of 2.2-2.8 percentage points compared to the 96.1% of Comparative Example 3. This is attributed to Mg 2+ After occupying the Li site, the Li-O bond length is lengthened, and Li + The activation energy of migration decreases, Al 3+ Occupying the V site amplifies the lattice micro-distortion of Li. + The effective cross-section of the diffusion channel, together with the Li in the coating layer, enables the Li to diffuse effectively. + The diffusion coefficient is increased by about 1 to 2 orders of magnitude; at the same time, Al 3+ The introduced lattice defects promote electron hopping, and the electronic conductivity of the coating layer is increased by about 1 to 3 orders of magnitude, which reduces polarization under high current charging and discharging conditions.
[0106] Combination Figure 4 The SEM image of Example 1 shows that the coated material retains its single-crystal morphology, with obvious coating dots distributed on the surface, indicating that the Mg-Al dual-doped LVP coating layer has formed a relatively complete coverage on the substrate surface. Regarding high-temperature cycle life, Examples 1-3 achieved 534-574 cycles at 45°C to 80% capacity retention (1C / 1C cycle), an improvement of 77-117 cycles compared to Comparative Example 3's 457 cycles, with Example 3 showing the best performance (574 cycles). This is attributed to the Al... 3+ The Al-O bonds formed at the V site act as "skeleton pinning," effectively suppressing the degradation caused by V during charge-discharge cycles. 3+ To V 4+ Redox-induced repeated lattice expansion / contraction stress, Mg 2+ The occupancy of the Li sites further stabilizes the NASICON-type three-dimensional framework structure. The two work together to maintain the structural integrity and interfacial bonding strength of the cladding layer during long-term cycling, thereby continuously providing effective protection for the matrix.
[0107] Regarding high-temperature storage performance, the capacity retention rates of Examples 1-3 after 7 days of storage at 55℃ and 100% SOC were 91.5%-92.6%, an improvement of 3.3-4.4 percentage points compared to the 88.2% of Comparative Example 3. This indicates that the Mg-Al dual-doped LVP coating exhibits superior chemical stability under extreme high-temperature fully charged conditions compared to undoped LVP. The mechanism lies in the Al... 3+ The strong Al-O bonds enhance the thermodynamic stability of the coating layer skeleton, while the improved density and interface coverage of the coating layer after doping more effectively prevent the electrolyte components from eroding the substrate surface.
[0108] Analysis of the impact of coating amount on performance: Comparing Example 1 (coating amount 1.0%), Example 2 (coating amount 0.5%), and Example 3 (coating amount 1.5%), it can be seen that the coating amount has a significant impact on the final performance. Regarding rate performance, the 2C capacity retention rate from highest to lowest is: Example 2 (98.9%) > Example 1 (98.7%) > Example 3 (98.3%), indicating that a smaller coating amount results in lower interfacial Li... + Lower transmission resistance; regarding high-temperature cycle life, the number of cycles to 80% at 45℃, from highest to lowest, is Example 3 (574 cycles) > Example 1 (564 cycles) > Example 2 (534 cycles), indicating that a larger coating amount provides more adequate protection for the substrate; regarding high-temperature storage performance, the capacity retention rate, from highest to lowest, is Example 3 (92.6%) > Example 1 (92.3%) > Example 2 (91.5%), showing the same trend as cycle life. In summary, a coating amount within the range of 1.0% to 1.5% achieves a balance of overall performance. Example 3, with a coating amount of 1.5%, achieves the best high-temperature cycling and storage performance, suitable for applications with higher durability requirements; Example 2, with a coating amount of 0.5%, achieves the best rate performance, suitable for applications with higher fast-charging performance requirements; Example 1, with a coating amount of 1.0%, achieves a balance among various performance aspects.
[0109] The above results show that the synergistic structural design of matrix Mg doping and surface Mg-Al dual-doped active LVP coating can comprehensively improve the electrochemical performance of spinel lithium manganese oxide cathode material from both bulk and surface levels. At the same time, the preparation process is also effectively simplified, which has high practical value.
[0110] The above description describes some specific embodiments of this application, but in actual applications, the application should not be limited to these embodiments. For those skilled in the art, other modifications and alterations made based on the technical concept of this application should fall within the protection scope of this application.
Claims
1. A positive electrode material, characterized in that, The positive electrode material includes a matrix and a coating layer covering the surface of the matrix; The matrix is lithium manganese oxide doped with Mg, and the lithium manganese oxide has a spinel structure, wherein Mg... 2+ Replace part of the Mn in the lithium manganese oxide 3+ Occupy octahedral sites in the spinel structure; The coating layer is lithium vanadium phosphate doped with Mg and Al elements, wherein Mg 2+ Al occupies some of the Li sites in the lithium vanadium phosphate to introduce cation vacancies. 3+ It occupies a portion of the V sites in the lithium vanadium phosphate to form Al-O bonds.
2. The cathode material according to claim 1, characterized in that, The mass of the coating layer accounts for 0.5% to 1.5% of the mass of the substrate.
3. The cathode material according to claim 1, characterized in that, The general formula of the cathode material is [LiMn]. (2-a) Mg a O4]@Li (3-2x) Mg x V (2-y) Al y (PO4)3, where 0.02≤a≤0.04, 0.01≤x≤0.05, 0.01≤y≤0.05, and the [LiMn] (2-a) Mg a O4] is the matrix, and Li (3-2x) Mg x V (2-y) Al y (PO4)3 is the coating layer.
4. A method for preparing a positive electrode material, characterized in that, The preparation method includes: The Li source, Mn source and magnesium source are mixed to obtain the first mixture; The first mixture is sintered once to form lithium manganese oxide with a spinel structure and doped with Mg, wherein Mg is doped during the first sintering process. 2+ Replacement part Mn 3+ The matrix is obtained by occupying the octahedral sites in the spinel structure; The Li source, V source, P source, Mg source, Al source and solvent are mixed to obtain a second mixture; The second mixture is dried and then subjected to secondary sintering to form lithium vanadium phosphate doped with Mg and Al elements. During the secondary sintering process, Mg... 2+ Occupying a portion of the Li sites in the lithium vanadium phosphate to introduce cation vacancies, and Al 3+ Al-O bonds are formed by occupying some of the V sites in the lithium vanadium phosphate to obtain a coating material; and, The substrate and the coating material are mixed and sintered three times to coat the surface of the substrate with the coating material, thereby obtaining the positive electrode material.
5. The preparation method according to claim 4, characterized in that, The sintering temperature for the first sintering is 750℃~850℃, and the time is 8h~12h; and / or, The secondary sintering temperature is 700℃~800℃, and the time is 6h~15h.
6. The preparation method according to claim 4, characterized in that, The temperature for the three sintering processes is 400℃~600℃, and the time is 4h~8h.
7. The preparation method according to claim 4, characterized in that, The second mixture is dried by spray drying, and the spray drying parameters are: air inlet temperature 150℃~180℃, feed speed 500rpm~140rpm, atomization frequency 180Hz~160Hz, and fan frequency 30Hz~55Hz.
8. The preparation method according to claim 4, characterized in that, After the step of drying the second mixture and then performing a secondary sintering to form lithium vanadium phosphate doped with Mg and Al elements, the method further includes: The step of milling and nano-sizing the sintered product of lithium vanadium phosphate doped with Mg and Al elements includes: The sintered product is mixed with deionized water and milled to make the D50 of the sintered product 0.1μm~0.2μm, and a slurry nano-sized by milling is obtained. The coating material is obtained by drying and pulverizing the nano-sized slurry.
9. The preparation method according to claim 4, characterized in that, The Li source, Mn source, and magnesium source are mixed using a dry mixing method, wherein the mixing frequency is 1000Hz~1200Hz and the mixing time is 8min~10min; and / or, The substrate and the coating material are mixed using a dry mixing method, with a mixing frequency of 1200Hz~1400Hz and a mixing time of 10min~30min.
10. An electrochemical device, characterized in that, It includes a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises a positive electrode material as described in any one of claims 1 to 3 or a positive electrode material prepared by the preparation method as described in any one of claims 4 to 9.
